NMR observation of substrate in the binding site of an active sugar-H+ symport protein in native membranes. - Spooner, P; Rutherford, N; Watts, A; Henderson, P (1994)
NMR methods have been adopted to observe directly the characteristics of substrate binding to the galactose-H+ symport protein GalP, in its native environment, the inner membranes of Escherichia coli. Sedimented inner-membrane vesicles containing the GalP protein, overexpressed to levels above 50% of total protein, were analyzed by 13C magic-angle spinning NMR, when in their normal "fluid" state and with incorporated D-[1-13C]glucose. Using conditions of cross-polarization intended to discriminate bound substrate alone, it was possible to detect as little as 250 nmol of substrate added to the membranes containing about 0.5 mumol (approximately 26 mg) of GalP protein. Such high measuring sensitivity was possible from the fluid membranes by virtue of their motional contributions to rapid relaxation recovery of the observed nuclei and due to a high-resolution response that approached the static field inhomogeneity in these experiments. This good spectral resolution showed that the native state of the membranes presents a substrate binding environment with high structural homogeneity. Inhibitors of the GalP protein, cytochalasin B and forskolin, which are specific, and D-galactose, but not L-galactose, prevent or suppress detection of the 13C-labeled glucose substrate, confirming that the observed signal was due to specific interactions with the GalP protein. This specific substrate binding exhibits a preference for the beta-anomer of D-glucose and substrate translocation is determined to be slow, on the 10(-2) s time scale. The work describes a straightforward NMR approach, which achieves high sensitivity, selectivity, and resolution for nuclei associated with complex membrane proteins and which may be combined with other NMR methodologies to yield additional structural information on the binding site for the current transport system without isolating it from its native membrane environment.